Parsing Bangla using LFG: an introduction - Haque, Muhammad Nasimul; Khan, Mumit (BRAC University, 2010)
This paper is intended to introduce LFG (Lexical Functional Grammar) for parsing Bangla. The LFG formalism, which has evolved from extensive computational, linguistic, and psycholinguistic research, provides a simple set of devices for describing the common properties of all human languages and the particular properties of individual languages. This paper provides a set of instructions for using the formulation of LFG rules to parse Bangla. With the information contained in this paper, linguists previously unfamiliar with the striking formalism of this theory should find it possible to interpret and to compose the sorts of rules and lexical items standardly employed in LFG. In this paper we present successful parse of some simple sentences along with some unsuccessful parse of non-grammatical sentences.